PENGARUH PENGENALAN GAMBAR DENGAN KECERDASAN VISUAL ANAK USIA 3-5 TAHUN - NOVIA DWI ASTUTI, NOVIA DWI ASTUTI (Asuhan Kesehatan : Jurnal Ilmiah Ilmu Kebidanan dan Keperawatan, 2012)
Visual intelligences is capacity to recognize and object depiction of brain. Visual intellegences can stimulated with some method such as with image recognition. The purpose of this study was to determine the influence of image recognition with visual intelligences.The study design use was a pre-experiment with approach pre test and post test group. All student PAUD Kemala Bhayangkari 96 Bojonegoro is population, as many as 15 student with a sampling technique is the total sampling. Data removal independent variabel with treatment and  dependent variabel with observation, then done editing, coding, scoring, tabulating and analyzed with a cross table. Based on research result obtained from 15 respondents, before to the introduction picture of  visual intelligences is less by 9 respondents and after to the  introduction picture of visual intelligences is less by 1 respondents.The conclusion of this study is there are effect introduction of image with visual intellegences., are suggested for PAUD to stimulate the children to be more increasing intellegences. So mother was expected to stimulate the intellegences of children by buying education toys, provide tools for coloring and drawing tools. Key words : Visual intellegences, introduction of picture.